2012
DOI: 10.1016/j.bjid.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Aeromycological study at the intensive care unit of the “Dr. Manuel Gea Gonzalez” General Hospital

Abstract: Fungal spores were found in the air of the ICU and Cladosporium spp. was the most frequently isolated fungi. There was no difference according to sampling time or height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
2
3
0
2
Order By: Relevance
“…Therefore, the presented study is aimed at detecting airborne fungi in the environment of different areas of two hospitals (1 and 2) to illustrate the occurrence of fungal species. The results obtained are in accordance with the results of other aeromycology studies from Mexico and Brazil [36][37][38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the presented study is aimed at detecting airborne fungi in the environment of different areas of two hospitals (1 and 2) to illustrate the occurrence of fungal species. The results obtained are in accordance with the results of other aeromycology studies from Mexico and Brazil [36][37][38].…”
Section: Discussionsupporting
confidence: 91%
“…The fungal burden found in the sampled areas of the two hospitals is inconsistent with that reported in other countries [28,29]; however, the CFU/m 3 in the operating theatre is consistent with such reports (5-10 CFU/m 3 ), which can be explained by the stringent hygienic measures in operating theatres. Similarly, there are no established criteria at the institutional level in Mexico regarding the ranges of CFU/m 3 that are considered acceptable, since only one study of this type has been reported [38]. The homogeneity in the number of CFU/m 3 found during the two seasons (rainy and dry) can be explained by the similarity between these season in Mexico City, compared with countries of North America and Europe, where seasons are marked by abrupt changes in ambient temperature and a true separation occurs between intramural and extramural environments, which does not happen in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…in the air of the ICU is worrisome as patients in the ICUs are usually severely ill or immunosuppressed prone to develop invasive fungal diseases [5]. Air conditioning system or the renovated ICUs are the common sources for them.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the studies were conclusive about the role of air microflora in nosocomial infection in the Intensive Care Unit (ICUs), especially if it is multidrug resistant (MDR). So far, very few studies had been done in the ICU environment such as Ríos-Yuil et al [5] mentioned about the presence of various nosocomially significant fungus in the ICU of a general hospital and Huang et al [6] tried to find out the potential correlation between airborne and surface contamination in two ICUs of Taiwan, and whether patient infections were related to microbial contamination in the ICU. Based on the limited background knowledge about microbial contamination of the ICU environment and their contribution to nosocomial infection in the ICU, the main objectives of this study were microbiological characterization of the air samples in relation to the nosocomial infections in the different ICUs at different periods in our tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Son numerosos los trabajos realizados en el mundo sobre aeromicología (Burch & Levetin, 2002;Jones & Harrison, 2004;Stępalska & Wolek, 2005;Kasprzyk, 2008;Ianovici et al, 2011;Abdel Hameed et al, 2012;Ríos-Yuil et al, 2012;Grinn-Gofroń & Bosiacka, 2015) que intentan conocer la distribución de los conidios de los hongos de una localidad, su variación en el tiempo y cómo pueden influir determinadas condiciones meteorológicas en su liberación y dispersión.…”
Section: Introductionunclassified